Relays, signals, actuality: a return to Focillon Review of: Annamaria Ducci, Henri Focillon en son temps. La liberté des forms, Strasbourg: Presses Universitaires de Strasbourg, 2021, 391 pp., 20 col. plates, 10 b. & w. illus, 26, 00 €, ISBN 979-10-344-0079-9. Issue 27 (2022) - Emerling, Jae
No abstract available